Conservative management of a dentigerous cyst secondary to primary tooth trauma - Gondim, Juliana Oliveira [UNESP]; Siebra Moreira Neto, Jose Jeova; Maia Nogueira, Renato Luis; Aparecida Giro, Elisa Maria [UNESP] (Blackwell Publishing, 2008)
Pulp necrosis is a commonly observed sequela in traumatized primary teeth and is one of the possible etiologic factors for the development of dentigerous teeth. This article reports the case of a dentigerous cyst associated with the germ of a permanent maxillary central incisor that developed secondary to trauma to the predecessor primary incisor. The therapeutic approach included endodontic treatment of the primary tooth and marsupialization of the lesion. After 36 months of follow up, the permanent incisor presented with normal physiologic conditions, absence of dental anomalies and erupted in its correct position in the oral cavity. In conclusion, with proper case selection, marsupialization might be a good treatment option for conservative management of dentigerous cysts.